Anterior cruciate ligament reconstructed female athletes exhibit relative muscle dysfunction after return to sport - Raymond-Pope, C. J.; Dengel, D. R.; Fitzgerald, J. S.; Nelson, B. J.; Bosch, T. A. (International Journal of Sports Medicine, 2021)
We sought to examine the relationship between upper-leg compartmental lean mass, muscle-specific strength, and explosive strength following anterior cruciate ligament reconstruction. Twleve adolescent female athletes with prior anterior cruciate ligament reconstruction were individually-matched by age (16.4±0.9 vs. 16.4±1.0 yrs.), body mass index (23.2±2.1 vs. 23.2±2.7 kg/m2), and sport to 12 female athlete controls. One total-body and 2 lateral-leg dual X-ray absorptiometry scans measured total/segmental body composition. Isokinetic dynamometry measured knee extensor/flexor peak torque. Squat jumps on force platforms measured bilateral peak vertical ground reaction force. Paired t-tests assessed lean mass, peak torque, and force between previously-injured athletes` legs and between previously-injured and control athletes` legs. Previously-injured athletes` involved vs. non-involved leg demonstrated lower total (7.13±0.75 vs. 7.43±0.99 kg; p<0.01) and anterior (1.49±0.27 vs. 1.61±0.23 kg; p<0.01) and posterior (1.90±0.19 vs. 2.02±0.21 kg; p=0.04) upper-leg lean mass. Involved leg peak torque (1.36±0.31; 1.06±0.27; 0.97±0.19 Nm/kg) was lower vs. non-involved leg (1.71±0.36; 1.24±0.33; 1.04±0.15 Nm/kg; p<0.01-0.02) for extension at 60 and 120°/sec and flexion at 60°/sec and vs. controls` `matched` leg (1.77±0.40 Nm/kg; p=0.01) for extension at 60°/sec. Involved leg force (296±45N) was lower vs. non-involved leg (375±55N; p<0.01) and vs. controls` `matched` leg (372±88N; p=0.02). One-year post-anterior cruciate ligament reconstruction, adolescent female athletes` involved leg demonstrated relative muscle dysfunction